Are momentum traders different? Implications for the momentum puzzle - Lukas Menkhoff (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2010)
This paper examines the puzzlingly high unexploited momentum returns from a new perspective. We analyze characteristics of momentum traders in a sample of 692 fund managers. We find that momentum traders are 'defined' by their short-term horizon, by a behavioural view on the market and by a somewhat lower degree of risk aversion, whereas they are like other fund managers with respect to sophistication. This is consistent with the interpretation that momentum returns may compensate for the risk of momentum trading on short-term horizons and that the short-term oriented momentum traders are not in a position to perform long-term arbitrage.
Keywords: G14; G23; D85; 330; momentum trading; market efficiency; behavioural finance; risk; Investmentfonds; Führungskräfte; Anlageverhalten; Wertpapierhandel; Zeit; Risikoaversion; Welt